Study of Interaction Between Sodium Fluorescein and Human Serum Albumin by Multi-Spectroscopic Method - Ji1, Zhen; Liang1, XuHua; Sun2, Yang; Fan1, Jun (Asian Journal of Chemistry, 2014)
The efficacy of sodium fluorescein (SF) binding to human serum albumin (HSA) is critical for the clinical application of sodium fluorescein in confocal laser endomicroscopy (CLE). The interactions between sodium fluorescein and human serum albumin under simulative physiological conditions were investigated by the methods of fluorescence spectroscopy, UV-visible absorption and circular dichroism spectroscopy. Fluorescence data revealed that the fluorescence quenching of human serum albumin by sodium fluorescein was resulted of the formation of the SF-HSA complex. According to the modified Stern-Volmer equation, the binding constants (Kb) between sodium fluorescein and human serum albumin at four different temperatures were obtained to be 1.75, 1.60, 1.46, 1.33 × 105 M-1, respectively. The thermodynamic parameters, enthalpy change (DH) and entropy change (DS) for the reaction were calculated to be -17.55 kJ mol-1 and 41.48 J mol-1 K-1 according to van’t Hoff equation, indicating that electrostatic interactions were the dominant intermolecular force in stabilizing the complex. The effect of sodium fluorescein on the conformation of human serum albumin was also analyzed by synchronous fluorescence, three-dimensional fluorescence and circular dichroism spectra. The results showed that the presence of sodium fluorescein decreased the a-helical content of human serum albumin (from 46.15-38.79 %) and induced the slight unfolding of the polypeptides of protein, which confirmed some micro-environmental and conformational changes of human serum albumin molecules.